Prognostic significance of rituximab and radiotherapy for patients with primary mediastinal large B-cell lymphoma receiving doxorubicin-containing chemotherapy. Issue 8 (August 2013) - Xu, Li-Ming; Fang, Hui; Wang, Wei-Hu; Jin, Jing; Wang, Shu-Lian; Liu, Yue-Ping; Song, Yong-Wen; Ren, Hua; Zhou, Li-Qiang; Li, Ye-Xiong
Abstract The aim of this study was to evaluate the prognostic importance of rituximab and radiotherapy in patients with primary mediastinal large B-cell lymphoma (PMBCL) receiving doxorubicin-containing chemotherapy. Seventy-nine patients with PMBCL received CHOP chemotherapy with (n = 39) or without rituximab (n = 40), and 60 patients received additional radiotherapy. Patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) had significantly superior survival rates. The 5-year overall survival (OS) and progression-free survival (PFS) rates were 83.7% and 76.7% for R-CHOP, compared with 48.3% (p = 0.011) and 44.2% (p = 0.012) for CHOP, respectively. Similarly, the 5-year OS and PFS rates for early stage patients were 93.8% and 84.6% with R-CHOP, and 52.0% (p = 0.002) and 46.6% (p = 0.003) with CHOP, respectively. Patients treated with chemotherapy and radiotherapy had better survival and local control (LC) rates compared with chemotherapy alone. The 5-year OS, PFS and LC rates for early stage patients were 73.6%, 69.9% and 92.6% for chemotherapy and radiotherapy, and 50.8% (p = 0.076), 36.9% (p = 0.008) and 56.4% (p < 0.001) for chemotherapy alone, respectively. Early stage patients treated with R-CHOP and radiotherapy had 5-year OS, PFS and LC rates of 96.4%, 85.9% and 93.1%. R-CHOP plus consolidation radiotherapy was associated with excellent survival and LC rates.